The transformation of corporate governance in France and Germany: The role of workplace institutions - Michel Goyer (Max Planck Institute for the Study of Societies, 2002)
This paper examines the process of refocusing on core competencies by large French and German firms. I compare two theories of comparative corporate governance on the question of refocusing: functional convergence and national institutionalist perspective. The empirical evidence presented in this paper points to two nationally specific patterns of change that do not meet fully the prediction of either perspective. Large French and German companies have changed but in different ways without experiencing any process of convergence. The differences in the process of refocusing in France and Germany are measured on three dimensions: speed of dismantling of conglomerates, adoption of financial transparency, and recourse to redundancies. I argue that the institutional arrangements of workplace organization constitute the critical variable accounting for the differences in the pattern of change in the two countries. In particular, the institutional arrangements of the organization of the shop floor provide management with constraints and opportunities to conduct the business strategy of the firm. – – Diese Arbeit untersucht den Prozess der Konzentration auf die Kernkompentenzen bei großen deutschen und französischen Unternehmen. Im Hinblick auf diesen Prozess lassen sich zwei theoretische Zugriffe unterscheiden: die Theorie der funktionalen Konvergenz und die institutionalistische Perspektive. Die Untersuchung zeigt, dass zwei national spezifische Veränderungsmuster existieren. Keiner der beiden Ansätze wird hinsichtlich seiner Vorhersagen gänzlich bestätigt. Konvergente Entwicklungen in großen deutschen und französischen Unternehmen sind nicht festzustellen. Unterschiedliche Veränderungsmuster zeigen sich in drei Dimensionen: der Geschwindigkeit der De-Diversifizierung, dem Grad an Transparenz und den Auswirkungen auf die Beschäftigung. Es wird argumentiert, dass die Ursache für diese Unterschiede in den Merkmalen der Arbeitsorganisation beider Länder liegt. Diese institutionellen Arrangements konfrontieren Führungskräfte mit unterschiedlichen Restriktionen und Möglichkeiten der Unternehmensführung.
Keywords: 300